2014
DOI: 10.1016/j.commatsci.2014.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interface dislocation Burgers vectors on elastic fields in anisotropic bicrystals

Abstract: A recent anisotropic elasticity formalism for quantifying interface dislocation arrays is used to compute the variations in long-range elastic fields and short-range strain energies of misfit dislocations due to changes in the Burgers vectors of the interface dislocations. The importance of selecting proper reference states for tilt and twist grain boundaries as well as a heterophase interface formed by tetragonal crystals is discussed in terms of partitioning of strain and rotation fields. For constrained int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…We calculate interface stress fields using an efficient, semi-analytical method developed previously 22 31 32 . This method accounts for the elastic anisotropy of solids A and B as well as for differences in elastic constants between them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculate interface stress fields using an efficient, semi-analytical method developed previously 22 31 32 . This method accounts for the elastic anisotropy of solids A and B as well as for differences in elastic constants between them.…”
Section: Resultsmentioning
confidence: 99%
“…It generates elastic field solutions consistent with a pre-specified interface crystallographic character (that is, misorientation and interface plane orientation 33 ) and with vanishing far-field stresses. The method has been successfully applied to a variety of homo- and hetero-phase interfaces 22 31 32 and has been validated through comparisons with atomistic simulations 18 .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, ambiguity arises whether the Burgers vector should be defined by the film or the substrate lattice constant. It has been suggested that an appropriate Burgers vector would enable far field stresses to become zero [12,13]. However, the far field stresses are obviously not zero in the continuous films except when a precise number of misfit dislocations are formed to cancel exactly the misfit strain.…”
Section: Introductionmentioning
confidence: 99%
“…We only show in this letter that the dislocation force varies by charge significantly which can perturb the polarization charge in nitride heterostructures and the stress/electric fields in piezoelectric- based electronic devices. Any further predictions of dislocation motion require dynamic analysis of ensembles of dislocations with discrete Burgers vector or continuous distribution of disregistry 31 using discrete/continuum models and field theories 32 as well as utilizing the dislocation density-based model to account for the dislocation interactions. 33 The presented analytical method characterizes the piezoelectric polarization in a bilayer system while emphasizes on the importance of charge and its effect on the dislocation force.…”
mentioning
confidence: 99%